2015
DOI: 10.1371/journal.pone.0142363
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Remitting and Relapsing Hyperglycemia in Post-Renal-Transplant Recipients

Abstract: BackgroundHyperglycemia following solid organ transplant is common among patients without pre-existing diabetes mellitus (DM). Post-transplant hyperglycemia can occur once or multiple times, which if continued, causes new-onset diabetes after transplantation (NODAT).ObjectiveTo study if the first and recurrent incidence of hyperglycemia are affected differently by immunosuppressive regimens, demographic and medical-related risk factors, and inpatient hyperglycemic conditions (i.e., an emphasis on the time cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 78 publications
(16 reference statements)
2
27
0
Order By: Relevance
“…We introduce a dataset of liver transplantation patients to complement a dataset of kidney transplantation patients previously used in published analyses by Boloori et al [22]. Together, these datasets allow, for the first time, a comparison of data across transplant types from the same medical institution with respect to PTDM risk and factors that might affect its incidence.…”
Section: Introductionmentioning
confidence: 99%
“…We introduce a dataset of liver transplantation patients to complement a dataset of kidney transplantation patients previously used in published analyses by Boloori et al [22]. Together, these datasets allow, for the first time, a comparison of data across transplant types from the same medical institution with respect to PTDM risk and factors that might affect its incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, HDL cholesterol is included in risk scores, drawn from the Framingham Offspring Study Diabetes Mellitus and the Diabetes Prediction Model risk scores [10,37], and is found to be useful for the prediction of PTDM in RTRs [38]. Baloore et al found that HDL cholesterol was inversely associated with both first and recurrent hyperglycemia after renal transplantation [39]. HDL cholesterol modulates glucose metabolism by various mechanisms, such as countering the deleterious effects of oxidized LDL on insulin production and activation of AMP-activated protein kinase [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the Medical Literature. We note that our work is also related to three streams in the medical literature: (1) incorporating the measurement errors of medical tests in decisionmaking for medication regimens (see, e.g., Bennett et al (2007)), (2) analyzing the diabetogenic effect of immunosuppressive drugs (see, e.g., Chakkera et al (2009) andBoloori et al (2015)), and…”
Section: Related Studiesmentioning
confidence: 99%
“…), (3) immunosuppressive drugs (e.g., tacrolimus) and diabetes medications (e.g., insulin) prescribed by physicians, and (4) results of medical tests (FPG, HbA1c, and Architect). Further details about our data set can be found in our earlier study (Boloori et al 2015).…”
Section: Data and Parameter Estimationmentioning
confidence: 99%